Penerapan Media Wordwall Gameshow Quiz untuk Meningkatkan Minat dan Hasil Belajar IPAS Kelas IV - Annisa Luthfia Rahma; Suratno (Postgraduate, University of Mataram, 2024)
The application of media is motivated by the use of video-based learning which has not been able to increase students' interest and learning outcomes. The lack of application of innovative and creative learning media can result in student learning outcomes not being achieved optimally, especially in class IV science and science learning on the Solar System material. The purpose of this research is to find out how to apply the Wordwall Gameshow Quiz media to increase learning interest and learning outcomes in the Solar System material in class IV. This research uses a qualitative type of research using a descriptive qualitative approach. The data sources for this research come from class teachers and class IV students. Data collection techniques use observation, interviews, documentation and questionnaires. The learning results from this research showed that 15 students out of 20 children understood the learning delivered using Wordwall media. Regarding interest in learning itself, there has been an increase shown by the number of students fulfilling more of the indicators, thus showing interest in feeling happy about lessons that are fun and enjoyable, as well as involving them directly in the application of the Wordwall Gameshow Quiz media. Through research and assessments, it shows that students like this media. Thus, it can be concluded that the Wordwall learning media is very suitable and effective for use in teaching and learning activities, especially in class IV science learning material on the solar system.